تأثير زيت بذور الرمان الوقائي في مستوى أنزيمات ALT,ASTفي الكبد المتضرر بمضاد الاكتئابLexotan عند الهامستر السوري . - علي اكتمال; دباغ مروان; أحمد ربا (Latakia University Journal -Biological Sciences Series, 2019)
The present study was designed to investigate the effects of oral administration of pomegranate seeds oil(PSO) on some liver,s functions and the role of granate seeds,s oil incorrecting the negatives effects. 30Hamsetrs were used in this study. They divided into five groups each of them have(6) animals.The1. group(control) became food and water free.The second one (1.Test)hat administrated with seeds,s oil (10mg/kg).The third group (2.test) became antidepressant (lexotan) 1mg/kg. The 4.group (3Test) that administrated seeds oil +antidepressant at the same time. The administration for4. group was every day for4.Weeks.While the5.group(4.Test) became antidepressant for4.Weeks after that it became granate seeds,s oil for4 another Weeks. The blood samples were collected from the heart ,They were kept for biochemical studies of liver enzymes: Alanine amino Transferase, Aspartate amino Transferase(ALT,AST).The concentrations (levels)of ALT in blood serum of 1(ALT,29.76%).Test were significanty decreased when compared to control(p<0.05) The results showes significant increasing (p<0.05)in the concentration of ALT and AST in blood serume by the(2.Test)when compared to control(ALT,37.3%;AST,70%) .The3.Test group showed significant decreased of AIT,AST levels when compared with2(ALT,16.38%;AST,47.51%).Test group but these concentration stilled higher than control significanty (p<0.05).Significant decreasing in concentration of ALT and AST in blood serum of 4.group when compared with 2.group (ALT,24.32%;AST,46.3%).but stilled higher than those of control group significantly p<0.05. صممت الدراسة الحالية لتقصي آثار التجريع الفموي لزيت بذور الرمان في بعض وظائف الكبد و دوره لتصحيح الآثار السلبية الضارة المحدثة بمضاد الاكتئاب . استخدم في هذه الدراسة ثلاثون (30) فرداً من ذكور الهامستر السوري قسمت إلى خمس مجموعات تحوي كل مجموعة ستة أفراد تركت المجموعة الأولى تتناول الغذاء والماء بشكل حر واعتبرت شاهدة, فيما جرعت المجموعة الثانية بزيت بذور الرمان PSOبتركيز (10mg/kg) واعتبرت مجموعة تجريبية أولى ,وجرعت المجموعة الثالثة بمضاد الاكتئاب (LEXOTAN 1mg/kg) واعتبرت مجموعة تجريبية ثانية, أما المجموعة التجريبية الثالثة جرعت بمضاد الاكتئاب وزيت بذور الرمان في نفس الوقت, جرعت هذه المجموعات يومياً لمدة4 أسابيع, والمجموعة التجريبية الرابعة جرعت بمضاد الاكتئاب Lexotan لمدة 4 أسابيع ثم جرعت بزيت بذور الرمان يومياً لمدة 4 أسابيع أخرى .جمعت عينات الدم من القلب مباشرة وحفظت لإجراء الدراسة الكيميائية الحيوية لأنزيمات الكبد ألانين أمين ترانسفيراز-أسبارتات أمين ترانسفيراز (ALT,AST).أظهرت نتائج الدراسة انخفاضاً معنوياً P<0.05 في تراكيزALTعند المجموعة التجريبية الأولى مقارنة مع الشاهدة(ALT,29.76%) .أظهرت النتائج زيادة معنوية (P<0.05) في تركيز أنزيمتي الكبد في المصل عند أفراد المجموعة التجريبية الثانية مقارنة مع الشاهدة (ALT,37.3%;AST,70%). أما بالنسبة للمجموعة التجريبية الثالثة (Test3) (مضاد+زيت ) فقد أظهرت النتائج انخفاضاً معنوياًP<0.05 في تراكيزALT,AST مقارنة بالمجموعة التجريبية الثانية (TEST.2)(AST,47.51% ALT,16.38%;).لكن هذه التراكيز لا تزال أعلى من تراكيز الشاهدة بفارق معنوي P<0.05.سجل انخفاض معنوي في تركيز كل من ALT و AST في مصل دم المجموعة التجريبية الرابعة. مقارنة بالمجموعة الثانية(%ALT,24.32%;AST,46.3) لكنه أيضاً لا يزال أعلى من تراكيز المجموعة الشاهدة بفارق معنوي P<0.05.